Cutaneous manifestations of HIV disease - Cockerell, Clay J. (Manson, 2013)
Dermatologists are often the first medical professionals to see patients with HIV infection, as skin diseases are common in acquired immunodeficiency syndrome. This book aims to help dermatologists recognize the cutaneous manifestations of HIV infection and AIDS, so that diagnosis can be made quickly and therapy begun as soon as possible.